2013
DOI: 10.1002/pc.22457
|View full text |Cite
|
Sign up to set email alerts
|

Development and physico‐mechanical behavior of LDPE–sisal prepreg‐based composites

Abstract: Low-density polyethylene (LDPE)-coated sisal fiber prepreg was prepared by using solution coating process. These coated fiber prepregs were consolidated to make composites having different weight fraction of sisal fibers in a hot compression-molding machine. This experimental study reveals that higher loading of sisal fiber up to 57wt% in LDPE-sisal composites is possible by this technique. Mechanical and abrasive wear characteristics of these composites were determined. The tensile strength of composites incr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 16 publications
0
6
0
Order By: Relevance
“…The increased content of sisal fiber in the composites enhanced the mechanical properties and the specific wear rate at all sliding distances. [285] Magalhães et al prepared polypropylene (PP) composites with peach heart palm sheath, using a single screw extruder. The results indicated that this type of composites could be a potential candidate in many conventional applications to replace wood and composites based on synthetic fibers.…”
Section: Progress In 2011-2015mentioning
confidence: 99%
“…The increased content of sisal fiber in the composites enhanced the mechanical properties and the specific wear rate at all sliding distances. [285] Magalhães et al prepared polypropylene (PP) composites with peach heart palm sheath, using a single screw extruder. The results indicated that this type of composites could be a potential candidate in many conventional applications to replace wood and composites based on synthetic fibers.…”
Section: Progress In 2011-2015mentioning
confidence: 99%
“…However, with continued research and development in this area, the scoop is fast expanding to more structural parts like seat frames, load floors, pick‐up beds, floor pans, drive train, and steering components. Studies have shown that natural fiber‐reinforced composites can be applied to where high strength, high stiffness, and low component weight are required . An investigation into the mechanical properties of sisal, abaca, hemp, coir, kenaf, and jute fiber‐reinforced polypropylene (PP) composites , showed an increase in the tensile strength and modulus with increasing fiber volume fraction.…”
Section: The Progressive Role Played By Automakers Auto Suppliers Amentioning
confidence: 99%
“…), and morphological properties (shape, size, structure etc.). [11][12][13][14][15][16][17][18] The tensile strength and Young's modulus of PE are enhanced after silica (SiO 2 ) nanoparticles are added to PE. [19] Multiwall carbon nanotubes (MWCNTs) and graphene with its rare mechanical and electrical properties becomes a potential candidate to be applied for diverse applications.…”
Section: Introductionmentioning
confidence: 99%